Solid pseudopapillary neoplasm of the pancreas in Sub-Saharan Africa: A case report and review of literature - M, Umar Muktar; M, Bashir Bello; K, Abdullahi; Fahad, Hassan (Indian Journal of Case Reports, 2018)
Solid pseudopapillary neoplasm of the pancreas is a rare indolent malignant tumor mostly found in young women in the second and third decades of life. Only about 3000 cases have been reported in English literature, with none in the West African region. Here, we report to the best of our knowledge, the first histologically confirmed case of solid pseudopapillary neoplasm of the pancreas in West Africa. A 29-year-old woman with a slow-growing left upper abdominal mass of 10 months. Abdominal ultrasound and computed tomography scans revealed a cystic-solid mass arising from the tail of the pancreas. She underwent surgical excision of the mass, with post-operative histopathology findings in keeping with solid pseudopapillary neoplasm of the pancreas. This case report highlights the importance of improved abdominal imaging, histopathology and the need for increased awareness as a differential diagnosis of an intra-abdominal tumor, especially in young women.